Selective hydrodeoxygenation of p-cresol as a model for coal tar distillate on Ni–M/SiO2 (M = Ce, Co, Sn, Fe) bimetallic catalysts. Issue 37 (5th July 2019) - Pan, Liuyi; He, Yulong; Niu, Menglong; Dan, Yong; Li, Wenhong
Abstract : Ni–M/SiO2 with different binary metals M (M = Ce, Co, Sn, Fe) prepared by an incipient impregnation method was used in the hydrodeoxygenation (HDO) of p -cresol as model of phenols in coal tar to produce BTX. Abstract : Ni–M/SiO2 with different binary metals M (M = Ce, Co, Sn, Fe) prepared by an incipient impregnation method was used in the hydrodeoxygenation (HDO) of low-temperature coal tar distillate, which is rich in phenolic compounds. p -Cresol, as a model compound of the distillate, was used to evaluate the activity and selectivity of BTX products on the series of reduced Ni–M/SiO2 catalysts in a fixed bed reactor. The properties of the catalysts were characterized by N2 adsorption–desorption, ICP-AES, XRD, H2 -TPR, and XPS. Benzene and toluene as the direct deoxygenation (DDO) products and cyclohexane and methylcyclohexane as the hydrogenolysis (HYD) products were detected to evaluate the selectivity of the path in the deoxygenation process. In this series of catalysts, the order of reactivity was Ni–Ce > Ni–Sn > Ni–Co > Ni–Fe > monometallic Ni. Meanwhile, the addition of Ce and Co loaded in the Lewis acid sites of the catalyst affected the electron distribution of nickel atom and its atomic arrangement on the surface of the carrier. Compared to monometallic Ni, the DDO path become dominant on Ni–Ce and Ni–Co and the selectivity for BTX products increased from 58.8% to 77.4% and 71.1%, respectively. The binary metal Sn, unlike the former two metals, formed a Ni3 Sn crystal form with Ni, which resulted in significant enhancement of the HYD path while obviously increasing the reactivity.